(untitled) (Economic and Political Thought, 2023)
The relative and absolute levels of public expenditures and their structure have been the subject of frequent disputes among economists and politicians. Making expenditures more rational and effective is currently a complex process because of the special character of the public sector as well as crises and the characteristics of its highly uncertain external environment. This paper analyses the directions of changes in the level and structure of public expenditures in Poland and the European Union in the context of the COVID-19 crisis. A broader historical perspective on changes in public expenditures is presented, and the de lege ferenda approach is adopted to formulate proposals concerning public expenditure policies in black swan times, indicating the related risks and concerns.